MATERNAL AND INFANT HEALTH SECTION OF THE DEMOGRAPHIC AND HEALTH SURVEY REPORT OF GHANA, 2008: A COMMENTARY - Adu-gyamfi, Samuel; Brenya, Edward; Adjei, Gifty Nuako (Journal of Humanity, 2016)
This article is basically a commentary on some sections on infant and maternalhealthcare of the 2008 demographic and health survey of Ghana. The attention of bothpolicy makers and academics are drawn to the need to ensure the expansion of thematernal and infant healthcare in Ghana. In same commentary, attention of readershave been drawn to the proclivity of the free maternal health policy to positively shapematernal and infant care in Ghana.